2009
DOI: 10.1002/chir.20713
|View full text |Cite
|
Sign up to set email alerts
|

The enantiomeric composition of linalool and linalool oxide in the flowers of kiwifruit (Actinidia) species

Abstract: A survey of linalool enantiomers in kiwifruit (Actinidia) flowers was conducted to determine their potential as sources of these valuable floral fragrances, and revealed a wide range of enantiomeric ratios. While flowers of A. polygama and A. chrysantha contained almost exclusively one enantiomer, most species contained significant amounts of both (R) and (S) isomers. In some species enantiomeric ratios of floral linalool differed between genotypes, full siblings, and in one case clones, and ratios changed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
1
7
0
2
Order By: Relevance
“…6D) also showed that ( S )-( E )-nerolidol was the predominant enantiomer and hence supports the assumption that AcNES1 is likely to be responsible for floral ( S )-( E )-nerolidol biosynthesis in A. chinensis . In contrast to the ( S )-linalool produced by AcNES1, the predominant linalool enantiomer in A. chinensis flowers, as previously shown by Matich et al (2010) was ( R )-linalool.…”
Section: Resultssupporting
confidence: 53%
“…6D) also showed that ( S )-( E )-nerolidol was the predominant enantiomer and hence supports the assumption that AcNES1 is likely to be responsible for floral ( S )-( E )-nerolidol biosynthesis in A. chinensis . In contrast to the ( S )-linalool produced by AcNES1, the predominant linalool enantiomer in A. chinensis flowers, as previously shown by Matich et al (2010) was ( R )-linalool.…”
Section: Resultssupporting
confidence: 53%
“…Additionally, reduced levels in product tea infusions may also result from its conversion to stress-induced linalool oxides, which may be catalysed by CYP76C1 as shown in Arabidopsis (Boachon et al, 2015). Linalool and its derivatives (Matich, Bunn, & Hunt, 2010) with strong floral scents are key contributors for tea floral scent based on OAV analysis, and changes in their abundances most likely altered the tea aromas, as found by Takeo (1981). It would be interesting to understand the biochemistry underlying these manufacture-induced abundance changes of geraniol and linalool.…”
Section: Changes In the Volatile Profiles Of Infusions Under Differenmentioning
confidence: 98%
“…Generally, it is believed that natural products exist as either of two distinct enantiomers to play biologically important roles. However, nature sometimes gives us interesting examples of natural products existing as mixtures of enantiomers 1–7. This is particularly noticeable in marine natural products.…”
Section: Introductionmentioning
confidence: 99%